5(x-4)+6=2x+3(-3+x)

Simple and best practice solution for 5(x-4)+6=2x+3(-3+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-4)+6=2x+3(-3+x) equation:


Simplifying
5(x + -4) + 6 = 2x + 3(-3 + x)

Reorder the terms:
5(-4 + x) + 6 = 2x + 3(-3 + x)
(-4 * 5 + x * 5) + 6 = 2x + 3(-3 + x)
(-20 + 5x) + 6 = 2x + 3(-3 + x)

Reorder the terms:
-20 + 6 + 5x = 2x + 3(-3 + x)

Combine like terms: -20 + 6 = -14
-14 + 5x = 2x + 3(-3 + x)
-14 + 5x = 2x + (-3 * 3 + x * 3)
-14 + 5x = 2x + (-9 + 3x)

Reorder the terms:
-14 + 5x = -9 + 2x + 3x

Combine like terms: 2x + 3x = 5x
-14 + 5x = -9 + 5x

Add '-5x' to each side of the equation.
-14 + 5x + -5x = -9 + 5x + -5x

Combine like terms: 5x + -5x = 0
-14 + 0 = -9 + 5x + -5x
-14 = -9 + 5x + -5x

Combine like terms: 5x + -5x = 0
-14 = -9 + 0
-14 = -9

Solving
-14 = -9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| S/6+8=13 | | 3x^2-3x=o | | 3p+65=7p+37 | | -.9v=-14.4 | | -5*(x+2)=15*(x-6) | | -12x=180 | | 6s-8=22 | | T/2.3=9 | | 9/(x-2)+5=0.5 | | -20=3x+7(2x-15) | | 7n=17.5 | | x/5-1=-4 | | R/-8=13.2 | | 6*(x-2)=18 | | 2s-12=20 | | 6x+7=3x-5 | | 45b=58.5 | | -5x-3y=14 | | 7.8k=-124.8 | | 7s-6=15 | | -5x-107=9x+61 | | M/4.5=-7 | | x+4*9+6=15 | | -5.1x=510 | | 3x+5(6x-16)=85 | | 8x-9=8(x-3) | | 4*(x+2)=3(5-x) | | N+7=-4 | | -29-4x=-8x+59 | | S+1.3=-5.1 | | N+1*2=8 | | B+56.8=90.3 |

Equations solver categories